The role of international experience on SMEs’ internationalization - Sandoval Álvarez, Carlos Alberto (2025)
This study evaluates the mechanism through which managers' international experience impacts the degree of internationalization of small and medium-sized enterprises (SMEs). The empirical analysis uses a sample of 131 managers of Costa Rican exporting SMEs. The main findings of the proposed structural structure model suggest that the international experience of managers indirectly impacts the degree of internationalization of SMEs. The proactivity of managers in international markets is the key factor influencing the degree of internationalization of SMEs. Risk perceptions associated with the firm's international expansion impact managers’ proactivity levels in international markets.